Secondary metabolites and anti-cholinesterase activity of Chamaecytisus heuffelii subsp. jankae aerial flowering parts - Milutinović, Violeta; Niketić, Marjan; Petrović, Silvana (Archives of Pharmacy, 2022)
Chamaecytisus heuffelii subsp. jankae (Velen.) Niketić (Fabaceae) is a dwarfish shrub, which range includes eastern part of the Balkan Peninsula (Albania, Bulgaria, Serbia). The aim of the investigation was to chemically characterize aerial flowering parts of this plant: the dried methanol extract (TM), its alkaloid (AF) and non-alkaloid (NAF) fractions, and to assess their ability and the ability of detected flavonoids to inhibit enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), in vitro in the Ellman spectrophotometric test. Plant material was collected in eastern Serbia (Jelašnička Klisura gorge), dried, powdered and extracted with methanol, after dichloromethane pre-extraction. Using solvents of different polarities and pH value, AF (yield 14.35%) and NAF (yield 57.78%) were obtained from TM. By LC-MS analysis, flavonoids luteolin-8-C-glucosylpentoside (159.81 mg/g), genistin (22.38 mg/g), vitexin (6.32 mg/g), rutin (4.25 mg/g), and genistein (0.86 mg/g) were detected and quantified in TM, while luteolin-8-C-glucosylpentoside (212.70 mg/g), rutin (1.38 mg/g), and genistin (1.03 mg/g) in NAF. Using GC-FID-MS analysis, quinolizidine alkaloids sparteine, 17-oksosparteine, and lupanine were identified in AF. TM and NAF exhibited significant and comparable anti-cholinesterase activity (IC50AChE 0.54 and 0.72 mg/mL; IC50BuChE 0.45 and 0.68 mg/mL). All detected flavonoids evinced the ability to inhibit enzymes; the most active were genistein and vitexin (IC50AChE 54.75 and 88.35 μg/mL; IC50BuChE 27.83 and 49.77 μg/mL). Considering the quinolizidine alkaloids toxicity and AF poor anti-cholinesterase activity, it might be concluded, regarding safety profile and medical potential, that the fraction of the herb methanol extract, flavonoid-rich and alkaloid-free (NAF), is good candidate for further research.